Impact of 11C-methionine positron emission tomography/computed tomography on radiation therapy planning and prognosis in patients with primary brain tumors. Issue 6 (November 2014) - Schinkelshoek, Mink; Lopci, Egesta; Clerici, Elena; Alongi, Filippo; Mancosu, Pietro; Rodari, Marcello; Navarria, Pierina; van der Hiel, Bernies; Scorsetti, Marta; Chiti, Arturo
Aims and background: There is limited evidence regarding the impact of 11 C-methionine positron emission tomography/computed tomography (MET-PET/CT) on radiation therapy planning of primary brain tumors. Our aim was to assess the effect of this imaging modality on treatment volumes and clinical outcome of patients eligible for radiation therapy in this oncologic setting. Methods and study design: Between November 2009 and May 2012, 31 consecutive patients (male:female, 20:11; mean age, 53.0 years) with pathologically proven primary/relapsed glioma were treated with radiation therapy at the Humanitas Research Hospital. All patients were submitted to the same multi-imaging protocol including MET-PET/CT for biological target volume (PET) and contrast-enhanced magnetic resonance imaging/CT for gross tumor volume, in order to define the clinical target volume. Different volumes were compared and analyzed with respect to treatment planning modification after MET-PET/CT and impact on disease outcome. In 19/31 cases, patients were re-evaluated after completing radiotherapy, and in these cases, progression-free survival and overall survival were determined. The study was submitted to and data collection was approved by the local ethics committee. Results: All patients completed the treatment. In 29 of 31 patients, a biological target volume was defined (mean volume, 18.3 cc), which in 20 cases (65%) resulted in a modification of the clinical target volume (mean, 65.9 cc; range, 8.5–165.6). In the other two cases, PET was negative and did not influence treatment planning. The mean percentage of added volume was 9.2%, ranging between -29% and 38%. With a mean follow-up of 5.4 months, treatment modification according to MET-PET/CT was the only predictor demonstrating a significant correlation with both progression-free survival (P = 0.018) and overall survival (P = 0.003). None of the other factors evaluated in the analyses, including age, tumor histology, previous treatment, and tumor uptake, was correlated with the outcome. Conclusions: Despite the limited study population, our data indicate that MET-PET/CT can have a significant impact on radiation therapy planning in patients with primary brain tumors. Moreover, treatment modification according to PET appears to be a predictor of clinical outcome in this group of patients.